2001
DOI: 10.1017/s1481803500005303
|View full text |Cite
|
Sign up to set email alerts
|

Emergency physicians’ attitudes toward a clinical prediction rule for the identification and early discharge of low risk patients with chest discomfort

Abstract: Objectives:To determine Canadian emergency physicians’ estimates regarding the safety and efficiency of chest discomfort management in their emergency department (ED), and their attitudes toward and perception of the need for a chest discomfort clinical prediction rule that identifies very low risk patients who are safe to discharge after a brief ED assessment.Methods:300 members of the Canadian Association of Emergency Physicians (CAEP) were randomly selected to receive a confidential mail survey, which invit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…This "miss rate" is more than twice that reported by Pope and colleagues 8 from a large US study (2.1%). In a previous survey of Canadian emergency physicians, 18 only 5% reported using a systematic follow-up process to identify missed cases, but half estimated that their miss rate for AMI was greater than 2%. Most (94%) indicated that an earlydischarge prediction tool would be helpful as long as it did not increase the rate of missed AMI above 2%.…”
Section: Discussionmentioning
confidence: 99%
“…This "miss rate" is more than twice that reported by Pope and colleagues 8 from a large US study (2.1%). In a previous survey of Canadian emergency physicians, 18 only 5% reported using a systematic follow-up process to identify missed cases, but half estimated that their miss rate for AMI was greater than 2%. Most (94%) indicated that an earlydischarge prediction tool would be helpful as long as it did not increase the rate of missed AMI above 2%.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of Canadian emergency physicians indicated that most (94%) would use a clinical prediction rule for ACS, provided that it did not increase the miss rate above 2%. 42 In the United States, however, physicians' triage decisions may be influenced more by perceived medical and legal risk, and it is not known what miss rate would be acceptable to most US physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to use Global Registry of Acute Coronary Events (GRACE) or TIMI scores to predict ACS, but 3 to 4% of the low-risk patients had a 30-day ACS outcome, 15,16 a risk that may be unacceptable to clinicians. 21 Many rules are hampered by selection bias, a suboptimal methodological design, or low sensitivity. 28,29 There has been no widely used clinical prediction rule for safe early discharge of such patients, and the few rules that have been validated permit risk stratification of selected patients but do not allow for minimal investigations or early discharge.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Based on a previous Canadian survey of emergency physicians, 21 the goal was for ACS sensitivity to exceed 98% while identifying the maximum number of low-risk patients who did not require hospitalization or prolonged testing.…”
Section: Introductionmentioning
confidence: 99%